Immune profiling in multiple sclerosis: a single-center study of 65 cytokines, chemokines, and related molecules in cerebrospinal fluid and serum - Berek, Klaus; Bauer, Angelika; Rudzki, Dagmar; Auer, Michael; Barket, Robert; Zinganell, Anne; Lerch, Magdalena; Hofer, Livia; Grams, Astrid; Poskaite, Paulina; Wurth, Sebastian; Berger, Thomas; et al. (Frontiers in Immunology, 2023)
The understanding of the pathophysiology of multiple sclerosis (MS) has evolved alongside with the characterization of cytokines and chemokines in cerebrospinal fluid (CSF) and serum. However, the complex interplay of pro- and anti-inflammatory cytokines and chemokines in different body fluids in people with MS (pwMS) and their association with disease progression is still not well understood and needs further investigation. Therefore, the aim of this study was to profile a total of 65 cytokines, chemokines and related molecules in paired serum and CSF samples of pwMS at disease onset. Multiplex bead-based assays were performed and baseline routine laboratory diagnostics, magnetic resonance imagining (MRI) and clinical characteristics were assessed. Of 44 participants included, 40 had a relapsing-remitting disease course and four a primary progressive MS. Twenty-nine cytokines and chemokines were significantly higher in CSF and 15 in serum. Statistically significant associations with moderate effect sizes were found for 34 of 65 analytes with sex, age, CSF and MRI parameters and disease progression. In conclusion, this study provides data on the distribution of 65 different cytokines, chemokines and related molecules in CSF and serum in newly diagnosed pwMS.